Interference of functional dual-tasks on static posturography in people with Parkinson's disease. - Monleón Guinot, Sara; Valenzuela, Constanza San Martín; Aranda Asensi, Vivina; Villanueva Navarro, Manuel; Tomás, José M. (Physiotherapy Theory & Practice, 2026)
Background: Balance impairments lead to daily-life complications in people with Parkinson's disease (PwPD). However, the way the environment interferes with balance is still unknown. Objective: To analyze the interference of dual-tasks (DTs) on balance in PwPD and compare it with healthy participants. Methods: Sixty-seven people were evaluated, 42 comprised the Parkinson's disease group (PDG) and 25 were part of the Control group (CG). All followed the balanced HOME assessment trial, performing static posturography under 5 conditions: single-task, visual DT (DTvisual), verbal DT (DTverbal), and two manual tasks, one above 90º of shoulder flexion (DTupper) and the other below (DTlower). Swept area, velocity, displacement, dispersion, and force of the Center of Pressure (CoP) were recorded. Results: DT interfered with the balance of the PDG in all conditions, while the CG was affected mainly in manual tasks. In the PDG, the swept area had the highest interference, reaching 218.84 mm2 in the DTupper condition, meaning 255.34% more swept area than in the single-task condition. However, CoP velocity was the most sensitive parameter to secondary tasks, being perturbed in all dual conditions tested, and the only outcome that increased (19.49%) during the DTvisual (p <.05). In DTverbal condition the groups maintained similar balance, except for the CoP mediolateral displacement and dispersion (p <.05). Conclusion: Compared to healthy participants, untrained PwPD showed poorer postural control under DTs conditions. This impairment increased with task complexity, ranging from visual distraction to overhead manipulation. Mediolateral CoP movements may serve as an early indicator of balance deterioration in challenging environments.